CRUSTACEOS DECAPODOS BARREMIANOS DE LA REGION DEL TUCU-TUCU, PROVINCIA DE SANTA CRUZ (Ameghiniana, 2013)
BARREMIAN DECAPOD CRUSTACEANS FROM THE Tucu Tucu REGION, SANTA CRUZPROVINCE. - Three macruran species, Palaeastacus terraeregina e (Etherídge), Enoploclytiasp. and Hoploparia longimana (Sowerby ) and one anomuran Protocallianassa patagonican. sp. are described and illustrated from the Río Mayer Formation, Austral Basin, Patagonia.Based on the associated ammonite fauna, the material is assigned to the Late Barremian,Although the genera are cosmopolitan, they are not of chronostratigraphic value, the macruranspecies, as well as the anomuran, are important environmental indicators. Hoploporialongimana (Sowerby), Enoploclytia sp. and Protocallianassa patagonica n. sp. are mentionedand described for the first time in Argentina.